Francisco Martínez Gascón, Kautela. A photojournalist during the Spanish Civil War in Heraldo de Aragón - Martínez de Vega, Cristina (Revista General de Información y Documentación, 2016)
The aim of this essay is to analyze and describe the work of Francisco Martínez Gascón, press photographer during the Spanish Civil War, examining his professional task in photojournalism as member of the staff of the regional newspaper, Heraldo de Aragón. The methodological approach in this essay has consisted on the use of bibliographical, iconographic and oral sources. Those sources have been located, identified and analyzed with a critical perspective in order to develop this research. The result has been a complete biography and the outline of his professional performance during the Spanish Civil War.